Scaling climate-smart innovations in Mali - Ewell, Hanna Louise Deborah; Carbonell Barlis, Angelica; Dossou Yovo, Elliot R; Suh Neville Ndohnwi; Aboubacar Diallo; Toure Haissa; Zougmore, Robert Bellarmin (2025)
Mali’s scaling pathway evolved from piloting individual innovations to bundling CSA and CIS solutions such as improved rice varieties, advisories, irrigation and finance, delivered through farmers’ hubs with strong institutional and private sector partnerships. Since 2021, nearly 500,000 farmers (41% women) have adopted CSA and CIS, achieving yield gains of up to 45%, higher incomes and improved food and nutrition security, while women and youth have benefitted from tailored innovations and service delivery roles. Scaling is constrained by weak institutional coordination, finance gaps, and socio-political fragility, but Mali is poised to expand multi-stakeholder platforms, inclusive finance and gender-responsive bundles.